Optical solitons and modulation instability analysis of the (1+1)-dimensional coupled nonlinear Schrodinger equation - Sulaiman, Tukur Abdulkadir; Bulut, Hasan (Iop Publishing Ltd, 2020)
This study successfully reveals the dark, singular solitons, periodic wave and singular periodic wave solutions of the (1 + 1)-dimensional coupled nonlinear Schrodinger equation by using the extended rational sine-cosine and rational sinh-cosh methods. The modulation instability analysis of the governing model is presented. By using the suitable values of the parameters involved, the 2-, 3-dimensional and the contour graphs of some of the reported solutions are plotted.
Keywords: the coupled nonlinear Schrodinger's equation; optical soliton; modulation instability